1978
DOI: 10.1115/1.3424302
|View full text |Cite
|
Sign up to set email alerts
|

Axial Impact Buckling of a Column With Random Initial Imperfections

Abstract: Axial impact buckling of perfectly elastic bars with initial imperfections is considered in a probabilistic setting. It is assumed that the initial imperfection function involved a single parameter, which in turn is a continuous random variable with given probability distribution function. The structure is said to buckle if the absolute value of the total displacement exceeds a prescribed value. The probabilistic nature of the random, critical time when such a failure occurs for the first time, is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In stochastic model, extensive knowledge of the probabilistic characteristics of the initial imperfection is required. Elishakoff [1] considered the axial impact buckling of perfectly elastic bars with initial imperfections in a probabilistic setting. Chryssanthopoulos and Poggi [2,3] represented the application of a probabilistic methodology to the design and analysis of stiffened and fiber-reinforced composite cylinders under axial compression.…”
Section: Introductionmentioning
confidence: 99%
“…In stochastic model, extensive knowledge of the probabilistic characteristics of the initial imperfection is required. Elishakoff [1] considered the axial impact buckling of perfectly elastic bars with initial imperfections in a probabilistic setting. Chryssanthopoulos and Poggi [2,3] represented the application of a probabilistic methodology to the design and analysis of stiffened and fiber-reinforced composite cylinders under axial compression.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it can be shown that the buckling wavelength scales with the inverse square root of the impact speed [50]. Extensive studies using similar approaches have focused on rapid application of axial loading on cylinders and shells [51][52][53]. Extensive studies using similar approaches have focused on rapid application of axial loading on cylinders and shells [51][52][53].…”
Section: Snap-through Of a Curved Panelmentioning
confidence: 99%
“…We represent the uncertainty in the initial imperfection profile so that we treat the coefficients A 0 and A 1 as random variables [5] with following truncated normal joint probability density function (pdf):…”
Section: Appendixmentioning
confidence: 99%
“…The study of the axial impact buckling of beams with simply supported boundary conditions and uncertain initial imperfections has been delt with by Lindberg [13], Elishakoff [5,6] and Ben-Haim and Elishakoff [2] and other authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation